ADAPTIVE CAPACITY AND RESILIENCE TO THE EARTHQUAKE AMONG STUDENTS IN KLATEN REGENCY - Yunus Aris WIbowo; Eka Wulan Safriani; Lintang Ronggowulan; Ratih Puspita Dewi; Siti Hadiyati Nur Hafida; Wahyu Widiyatmoko; Puspita Indra Wardhani; Usmaningtyas Ayu Dwi Septiningrum; Sindi Ashyari Putri; Ibnu Abdullah Aris; Saifulloh Rizqi Wijayanto (GeoEco, 2023)
One of the risk components that are most vulnerable to earthquake disasters is children. Klaten Regency is one of the areas frequently shaken by earthquakes. Therefore, this study aims to measure students' adaptive capacity and resilience to earthquakes in the Klaten Regency. Respondents in this study were students of SMP M 8 Wedi, MTs M 10 Wedi, and SMP M 21gantiwarno, Klaten Regency. The adaptive capacity of students is measured based on institutional memory, innovative learning, and connectedness. In contrast, students' resilience level is measured based on emotion regulation, control over problems, optimism, empathy, self-efficacy, ability to analyze issues, and achievement. Data were collected using a questionnaire and processed using descriptive statistics. The level of adaptive capacity and resilience of the student community to natural disasters has different characteristics due to the influence of several factors such as the location of the school in a disaster-prone area, the integration of disaster material into learning, experience in disaster emergency response conditions, school policies on disaster mitigation and family or community factors environment. The best level of adaptive capacity is found in SMP Muhammadiyah 8 Wedi with 62.90%, and MTs Muhammadiyah 10 Wedi has a poor level of adaptive capacity with 44.32%. Moreover, based on gender characteristics, the level of adaptive capacity of male students is better than female students, with the lowest percentage being female at MTs Muhammadiyah 10 Wedi. The highest level of student resilience is found at MTs Muhammadiyah 10 Wedi at 61.36%, while SMP Muhammadiyah 21 Gantiwarno is classified as poor at 33.33%. Based on gender characteristics, the highest level of resilience is female at MTs Muhammadiyah 10 Wedi, with 91.67%.